Kontribusi R.A.A. Wiranatakoesoema V dalam Menerjemahkan Sejarah Nabi Muhammad Saw. di Tatar Sunda Tahun 1941 - Hidayat, Asep Achmad; Anggie Satiti, Ratu Asih (Historia Madania: Jurnal Ilmu Sejarah, 2019)
Translation has an important role in the dissemination of knowledge, religious teachings, and culture existing throughout the world. The ex-Regent of Bandung R.A.A. Wiranatakoesoema V gave contribution to Sundanese language with his translation work in the field of religion. He translated the works of E. Dinet and Sliman bin Ibrahim by using two writing models, namely combining modern European writing in the form of prose, in line with traditional Sundanese writing traditions, called dangding. His work was published in 1941 entitled Riwajat Kangdjeng Nabi Moehammad, peace be upon him. This book became an early historical literature of prophets printed using Latin and Arabic characters, and it contributed to the translation style in the Sundanese Land.